POTENTIAL NATURAL ANTIOXIDANT CONTENT IN SONGAN KINTAMANI TOMATO EXTRACT BANGLI - Martini , A.A Kompiang; Sukrama, I Dewa Made; Yoga, Widnyana; Janurianti, Ni Made Defy; Salesman, Frans (Journal of Medical Care Research and Review, 2021)
Tomato is one of the plants that have the potential as a source of antioxidant compounds. Tomatoes contain lycopene which is a powerful antioxidant. Lycopene has been shown to reduce the risk of heart disease, cancer, and disease in old age. Songan Village, Bangli is a tomato-producing area in Bali. This study aimed to determine the content of antioxidant compounds in tomatoes from Songan-Kintamani Bangli village. The research method used is a descriptive experiment. Tomato fruit was extracted by the maceration method using hexane and methanol. The results of the phytochemical screening test of tomato extract showed that the tomato extract contained bioactive compounds of alkaloids, phenolics, saponins, and flavonoids. The extracts were then tested for lycopene, polyphenols, flavonoids, and antioxidant activity levels. Tomato fruit extract had a lycopene content of 0.878 mg/100g, polyphenol content of 7.55 mg/L GAE, and flavonoid content of 1,278 mg/100 g QE. Tomato extract has strong antioxidant activity with an AAI value of 1.387 Keywords: phytochemical, lycopene, antioxidants, tomatoes, Songan, Bangli